Strategi Perencanaan Sumber Daya Manusia pada Marketplace 'Swipewash' untuk Optimasi Layanan Laundry" atau "Analisis Kebutuhan Sumber Daya Manusia dalam Pengembangan Ekosistem Digital Swipewash - Athira Shafa Berliana; Dimas Angga Negoro; Unggul Kustiawan; Ferryal Abadi (INSOLOGI: Jurnal Sains dan Teknologi, 2026)
The e-commerce industry in Indonesia is experiencing rapid growth, supported by a large population, a growing middle class, and increasing internet penetration. In a busy urban society, these services are becoming an essential need. Digital platforms can provide solutions with easy access, transparency, and efficiency for consumers. SwipeWash offers an e-commerce platform for laundry, bag spa, and shoe spa services equipped with superior features. Based on a combination of strengths, weaknesses, opportunities, and threats. Strategies to take advantage of the company's opportunities and strengths include utilizing e-commerce technology and the Internet of Things (IoT) to improve operational efficiency while expanding the market. To overcome weaknesses while taking advantage of existing opportunities, SwipeWash plans to apply for additional funding to improve technology and utilize data analytics. In an effort to realize SwipeWash's vision as a leading, innovative and trusted e-commerce laundry platform, human resource management is one of the key elements. The goals and objectives formulated are aimed at ensuring operational sustainability, supporting company growth, and creating a productive and competitive work environment. Through structured planning, SwipeWash is committed to presenting a solid, competent team that is in line with market needs, both in the short, medium and long term.